1990
DOI: 10.1021/bp00006a001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Temperature Control Policy for a Two‐Stage Recombinant Fermentation Process

Abstract: The optimal temperature control policy to be followed in the operation of a two-stage fermentation system in which gene expression is induced by a temperature-sensitive gene switching system was studied. A genetically structured model was used to describe product formation, and kinetic equations based on experimental data were used to quantify the specific gene expression rate and parameters that affect plasmid instability. A constant temperature control policy and temperature profiling control policy includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It has been shown that during prolonged periods of derepression of the λpL/pR promoters at temperatures up to 42°C, the propagation of plasmid-free cells is favored [16,126,127]. Furthermore, the fraction of plasmid-free cells under derepression at 38 or 40°C has been reported to be lower than at 41°C or above [16,127].…”
Section: Phenomena and Variables That Modulate The Productivity In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that during prolonged periods of derepression of the λpL/pR promoters at temperatures up to 42°C, the propagation of plasmid-free cells is favored [16,126,127]. Furthermore, the fraction of plasmid-free cells under derepression at 38 or 40°C has been reported to be lower than at 41°C or above [16,127].…”
Section: Phenomena and Variables That Modulate The Productivity In Thmentioning
confidence: 99%
“…Furthermore, the fraction of plasmid-free cells under derepression at 38 or 40°C has been reported to be lower than at 41°C or above [16,127]. For example, Sayadi et al [128] detected that 12 and 48% of the cells had lost the plasmid after 250 generations at 37 and 42°C, respectively.…”
Section: Phenomena and Variables That Modulate The Productivity In Thmentioning
confidence: 99%
“…1988) products. Recombinant plasmid stability and other parameters of the cultures have been independently analyzed in these conditions (Siegel and Dewey, 1985;Hortacsu and Ryu, 1990). In a previous work (Cubarsi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal temperature control policy for the two-stage system was considered in a previous study. 3 The dilution rate determines the apparent or averaged growth rate of a heterogeneous population of plasmid-harboring and plasmid-free cells. The growth rate, in turn, affects the plasmid content of the cells, the stability of the plasmid-harboring cells, and the cellular metabolic rates for the translation and transcription steps necessary for gene expression.…”
Section: Introductionmentioning
confidence: 99%